The influence of vocabulary skills and sentence structure with the ability to write a paragraphs description of vocational students - Rahmawati Rahmawati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The research aims to determine: (1) the ability to use vocabulary and sentence structure class X SMK Purnama 2 Jakarta-Selatan. (2) the ability to write a paragrafh description and (3) the effect of the ability to use vocabulary and sentence structure to the ability to write a paragrafh description class X SMK Purnama 2 Jakarta-selatan. The research data such as the results of tests of vocabulary and sentence structure in the form of written tests of vocabulary and sentence structure of each of 50 numbers and descriptions essay writing test. The data source is a class X student of SMK Purnama 2 Jakarta-Selatan. Data were analyzed using multiple linear regression analysis. The results showed that (1) the ability to use the vocabulary class X SMK Purnama 2 Jakarta - Selatan and average value is 38.27, while the ability to use sentence structure average rating: 37.86. (2) The ability to write essays description of the class X SMK Purnama 2 Jakarta-Selatan average value is 38.92 and (3) no effect between the ability to use vocabulary and sentence structure to the ability to write a paragrafh description of the class X SMK Purnama 2 Jakarta- Selatan.